(untitled) (Studia austriaca, 2017)
The aim of this paper is to explore the literary investigations of Günther Anders within the horizon of his philosophical thinking. Starting from Anders’s thesis about the «humanity without world», the paper analyzes Anders’s interesting remarks about Brecht’s literary theory and theatrical works, the poetry of Rilke, the literature of Döblin, and especially the masterpieces of Kafka. Relying upon the analysis of these authors, and thanks to an interdisciplinary viewpoint, the importance of the method of literary reference becomes crucial to an understanding of Anders’s concept of «humanity without world» and of the apocalyptic image of a «world without humanity».